Energy recovery from the pyrolysis of rice hulls - Castro, Arnold Allan R. (College of Engineering, 1981)
Plant name: GT Grain Millers Pyrolyzer -- Plant location: Kasisang, Malaybalay Bukidnon -- Product names: Rice Charcoal, Con Oil, Dem Oil, Rice Gas -- Capacity: 720 MT/yr -- Fixed capital investment: P 429,977.38 -- Operating costs: 90,106.18 -- Sales: 428,310.72 -- Payout time: 2.09 years -- Break-even point: 41% production -- Shut-down point: 22% production